The discourse of heroism in the novels of Ivan Bahriany - Шапошникова, Олена Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The paper is concerned with an anthropological understanding of such phenomenon as heroism in the works by Ukrainian writer Ivan Bahriany, the concept of pseudo-heroism, and the heroism features of the characters distinguished for their passionarіty. It is proved that the author considers the heroic manifestations to be an anthropological norm, with the antithesis of heroism within Bahriany’s outlook being vileness, timeserving, cynicism, and meanness of spirit. Ivan Bahriany was an apologist for an idea of herocracy as the power of Ukrainian spiritual aristocracy. Presented in the writer's novels, the discourse of heroism demonstrates the author 's neo-romantic dominant style.